ENHANCEMENT OF BIOGAS PRODUCTION FROM CO-ANAEROBIC DIGESTION OF FRESH CHICKEN MANURE WITH CORN STOVER - MOHD JOHARI, SITI AMINAH (2020)
Agrowing number of chicken farms in Malaysia leads to the abundance of chicken waste produced approximately 365,000 tonnes/yearand the obvious problems from chicken manure are unpleasant odor and flies‘ attractions. High corn production also leads to increase of waste including corn stover(CS). The knowledge for biogas production from co-digestion of these wastes are still limited in term of different ratio of fresh chicken manure (FCM) to CSand utilization manure from specific days of chicken.This study focused on generating biogas fromfresh manure of 20 days of chicken by varying water ratio parameter and different FCM combination with CS composition.